Porphyric encephalopathy in a 15-year-old girl: A case report - Saihari S Dukkipati; Jordan Terschluse; Drew Thodeson; Angela Beavers; Melissa Muff-Luett; Claire Ives; Sookyong Koh (SAGE Open Medical Case Reports)
A 15-year-old girl presented with new onset tonic-clonic seizures, encephalopathy, abdominal pain, and hypertension with a history of weight loss and emesis. Brain magnetic resonance imaging scans showed diffuse, bilateral cortical and subcortical gray and white matter signal abnormalities. Electroencephalography showed background slowing and disorganization. Extensive evaluation for infection, toxic metabolic, autoimmune disorders, and vasculitis were negative. She was noted to have dark red-colored urine with no red blood cells. Her urine porphobilinogen level was markedly elevated, consistent with the diagnosis of acute intermittent porphyria. She was treated with intravenous hemin with resolution of her neurologic and gastrointestinal symptoms. A hydroxymethylbilane synthase (porphobilinogen deaminase) pathogenic variant was found in porphyria gene panel confirming the diagnosis of acute intermittent porphyria. This case demonstrates a diagnostic challenge posited by a presentation of new onset seizure and encephalopathy due to acute intermittent porphyria, a rare and often overlooked condition in pediatrics.